Interactive Real-Time Simulation and Auralization for Modifiable Rooms. Issue 1 (March 2014) - Pelzer, Sönke; Aspöck, Lukas; Schröder, Dirk; Vorländer, Michael
To study the effects of any changes to a room or setting on the room acoustics, a framework was developed that enables immediate acoustic and visual feedback to the user. This is achieved by running interactive room acoustics simulations and auralizations in real-time. Physically based binaural room impulse responses (BRIRs) are calculated using the image source method and ray tracing and are divided into direct sound, early reflections and late reverberation. Any part of the BRIR is updated as quickly as possible depending on the user's interaction with the scene. This includes changes to sources and receivers (positions/orientations/directivities/HRTF), to surface materials and to the room geometry itself. Using streaming low-latency convolution, an immediate feedback is provided to the user. A parallelization concept features multi-threading and networked PC-clusters, so that the workload can be effectively distributed, offering a scalability to simulate small to huge scenes, depending on the available computation power. For convenient scene design and interaction, a plug-in for Trimble SketchUp was developed that enables real-time room acoustics and room acoustics parameter visualization to this easy-to-use CAD modeling tool.